Motoneuron Death after Human Spinal Cord Injury - Grumbles, Robert M. (J Neurotrauma, 2017)
The severe muscle weakness and atrophy measured after human spinal cord injury (SCI) may relate to chronic muscle denervation due to motoneuron death and/or altered muscle use. The aim of this study was to estimate motoneuron death after traumatic human SCI. The diameter and number of myelinated axons were measured in ventral roots post-mortem because ventral roots contain large diameter (> 7 μm) myelinated axons that typically arise from motoneurons and innervate skeletal muscle. In four cases (SCI levels C7, C8, T4, and L1) involving contusion (n = 3) or laceration (n = 1), there was a significant reduction in the number of large diameter myelinated axons at the lesion epicenter (mean ± standard error [SE]: 45 ± 11% Uninjured), one level above (51 ± 14%), and one (27 ± 12%), two (45 ± 40%), and three (54 ± 23%) levels below the epicenter. Reductions in motoneuron numbers varied by side and case. These deficits result from motoneuron death because the gray matter was destroyed at and near the lesion epicenter. Muscle denervation must ensue. In seven cases, ventral roots at or below the epicenter had large diameter myelinated axons with unusually thin myelin, a sign of incomplete remyelination. The mean ± SE g ratio (axon diameter/fiber diameter) was 0.60 ± 0.01 for axons of all diameters in five above-lesion ventral roots, but increased significantly for large diameter fibers (≥ 12 μm) in three roots at the lesion epicenter. Motoneuron death after human SCI will coarsen muscle force gradation and control, while extensive muscle denervation will stifle activity-based treatments.